Impact of Inter-Set Short Rest Interval Length on Inhibitory Control Improvements Following Low-Intensity Resistance Exercise in Healthy Young Males - Tomoo, Keigo; Suga, Tadashi; Dora, Kento; Sugimoto, Takeshi; Mok, Ernest; Tsukamoto, Hayato; Takada, Shingo; Hashimoto, Takeshi; Isaka, Tadao (Frontiers in Physiology, 2021)
The length of rest interval between sets (i.e., inter-set rest interval) is an important variable for resistance exercise program. However, the impact of the inter-set rest interval on improvements in cognitive function following resistance exercise remains unknown. In this study, we compared the effect of short rest interval (SRI) versus long rest interval (LRI) protocols on post-exercise cognitive inhibitory control (IC) improvements induced by low-intensity resistance exercise. Twenty healthy, young males completed both SRI and LRI sessions in a crossover design. The bilateral knee extensor low-intensity resistance exercise was programed for six sets with ten repetitions per set using 40% of one-repetition maximum. The inter-set rest interval lengths for SRI and LRI protocols were set for 1 and 3 min, respectively. The color-word Stroop task was administrated at six time points: baseline, pre-exercise, immediate post-exercise, and every 10 min during the 30-min post-exercise recovery period. The levels of blood lactate, which may be an important determinant for improving IC, throughout the 30-min post-exercise recovery period were significantly higher following SRI protocol than following LRI protocol (P = 0.002 for interaction effect). In line with this result, large-sized decreases in the reverse-Stroop interference score, which represent improved IC, were observed immediately after SRI protocol (d = 0.94 and 0.82, respectively, vs. baseline and pre-exercise) as opposed to the moderate-sized decreases immediately after LRI protocol (d = 0.62 and 0.66, respectively, vs. baseline and pre-exercise). Moreover, significant decreases in the reverse-Stroop interference score were observed from 10 to 30 min after SRI protocol (all Ps < 0.05 vs. baseline and/or pre-exercise), whereas no such decrease was observed after LRI protocol. Furthermore, the degree of decreases in the reverse-Stroop interference score throughout the 30-min post-exercise recovery period was significantly greater in SRI protocol than in LRI protocol (P = 0.046 for interaction effect). We suggest that the SRI protocol is more useful in improving post-exercise IC, potentially via greater circulating lactate levels, compared to the LRI protocol. Therefore, the inter-set rest interval length may be an important variable for determining the degree of cognitive function improvements following resistance exercise in healthy young males.